Respuesta :

Answer:

(a) [tex]P" = (-4,-3)[/tex]

(b) [tex](x,y) \to (4,-8)[/tex]

Step-by-step explanation:

Given

[tex]P = (4,3)[/tex]

Solving (a): Reflect across x and y-axis.

Reflection across x-axis has the following rules

[tex](x,y) \to (x,-y)[/tex]

So, we have:

[tex]P' = (4,-3)[/tex]

Reflection across y-axis has the following rules

[tex](x,y) \to (-x,y)[/tex]

So, we have:

[tex]P" = (-4,-3)[/tex]

Hence, the new point is: (-4,-3)

Solving (b): Rx . Do,2 (2,4)

[tex]R_x \to[/tex] reflect across the x-axis

Reflection across x-axis has the following rules

[tex](x,y) \to (x,-y)[/tex]

So, we have:

[tex](2,4) = (2,-4)[/tex] ---- when P is reflected across the x-axis

[tex]D_{o,2} \to[/tex] dilate by a scale factor of 2

The rule is:

[tex](x,y) \to 2 * (x,y)[/tex]

So, we have

[tex](x,y) \to 2 * (2,-4)[/tex]

Open bracket

[tex](x,y) \to (4,-8)[/tex]

ACCESS MORE